BioMEMS Biosensing Applications - Hosseini, Samira; Espinosa-Hernandez, Michelle Alejandra; Garcia-Ramirez, Ricardo; Cerda-Kipper, Ana Sofia; Reveles-Huizar, Sofia; Acosta-Soto, Luis.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2021)
This book highlights the latest advances in bioMEMS for biosensing applications. It comprehensively reviews different detection methods, including colorimetric, fluorescence, luminescence, bioluminescence, chemiluminescence, biochemiluminescence, and electrochemiluminescence, and presents various bioMEMS for each, together with recent examples. The book also offers an overview of the history of BioMEMS and the design and manufacture of the first bioMEMS-based devices.
History of Bio-microelectromechanical systems (BioMEMS) -- Bio-microelectromechanical systems (BioMEMS) in Bio-sensing applications-Colorimetric detection strategies -- Bio-microelectromechanical systems (BioMEMS) in Bio-sensing applications-Fluorescence detection strategies -- Bio-microelectromechanical systems (BioMEMS) in Bio-sensing applications-Luminescence detection strategies -- Bio-microelectromechanical systems (BioMEMS) in Bio-sensing applications-Bioluminescence detection strategies -- Bio-microelectromechanical systems (BioMEMS) in Bio-sensing applications-Chemiluminescence detection strategies -- Bio-microelectromechanical systems (BioMEMS) in Bio-sensing applications-Biochemiluminescence detection strategies -- Bio-microelectromechanical systems (BioMEMS) in Bio-sensing applications-Electrochemiluminescence detection strategies.
Keywords: Amorphous substances; Complex fluids; Nanochemistry; Biomedical engineering; Nanotechnology; Spectroscopy; Microscopy; Soft and Granular Matter, Complex Fluids and Microfluidics; Nanochemistry; Biomedical Engineering/Biotechnology.; Nanotechnology and Microengineering; Nanotechnology; Spectroscopy and Microscopy